Efficacy of different green manuring crops to soil fertility, yield and seed quality of T. aman rice (Asian Journal of Medical and Biological Research, 2021)
A series of experiments were conducted on the Agronomy farm and laboratory of Sher-e-Bangla Agricultural University to demonstrated a promising way of increasing soil organic matter, total N in pre sown and postharvest land by green manure cultivation and reducing the inorganic fertilizer inputs in rice production and finally observed the quality of grown T. aman seed in laboratory condition. Several green manures were found more potential in two years regarding their plant height, dry biomass production and better performance concerning organic matter, nitrogen and potassium contribution to soil and increased rice yield. Morphological characteristics of eight green manure crops were studied and incorporated at 45DAS for decomposition. One month after decomposition of green manure, rice (BRRI dhan66) plant was transplanted with 100% NPK (F1) and 50% NPK (F2) and pre sown rice soil, post-harvest soil nutrient statuses were studied. Result showed that Pre shown rice soil increased 0.5 to 0.6% SOM (2nd year), 0.04% soil N (both year) and 0.04% soil K (1st year) which ultimately increase rice yield 62% to 68% (with F1) and 10% to 42% in 1st and 2nd year. Post-harvest soil nutrient status shown the positive balance of (0.1% to 1%) organic matter and total N (0.04% to 0.7%) in the 1st years and 2nd years and P was found drastically increased in 2nd year, respectively. Germination%, germination energy%, seedling length, fresh and dry weight of six month stored rice seedling also found highest from S. rostataand S. aculeataunder laboratory condition. Incorporation of Sesbaniaaculeata, S. rostrata, V. unguiculataand Crotalaria junceaas GM with N significantly influenced the grain yield of rice and pre and post-harvest soil.Asian J. Med. Biol. Res. 2021, 7 (4), 298-311